2007
DOI: 10.1007/s11099-007-0060-y
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory effects of elevated CO<sub>2</sub> concentration on the inhibitory effects of high temperature and irradiance on photosynthetic gas exchange in carrots

Abstract: We determined the interactive effects of irradiance, elevated CO 2 concentration (EC), and temperature in carrot (Daucus carota var. sativus). Plants of the cv. Red Core Chantenay (RCC) were grown in a controlled environmental plant growth room and exposed to 3 levels of photosynthetically active radiation (PAR) (400, 800, 1 200 μmol m -2 s -1 ), 3 leaf chamber temperatures (15, 20, 30 °C), and 2 external CO 2 concentrations (C a ), AC and EC (350 and 750 μmol mol -1 , respectively). Rates of net photosynthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
1
6
1
Order By: Relevance
“…Wheat plants grown in elevated CO 2 have been shown to have a higher temperature optimum for photosynthesis which may be related to modifications in the temperature dependency of Rubisco activity (Alonso et al 2008) and a higher thermo-tolerance of PSII (Taub et al 2000). However, in the present study, the increased ITE seen in plants grown in elevated CO 2 was probably more attributed to an increased competitiveness of CO 2 against O 2 for the active site on the Rubisco protein, which was also suggested as the main effect of elevated CO 2 on photosynthesis in carrot (Thiagarajan et al 2007).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Wheat plants grown in elevated CO 2 have been shown to have a higher temperature optimum for photosynthesis which may be related to modifications in the temperature dependency of Rubisco activity (Alonso et al 2008) and a higher thermo-tolerance of PSII (Taub et al 2000). However, in the present study, the increased ITE seen in plants grown in elevated CO 2 was probably more attributed to an increased competitiveness of CO 2 against O 2 for the active site on the Rubisco protein, which was also suggested as the main effect of elevated CO 2 on photosynthesis in carrot (Thiagarajan et al 2007).…”
Section: Discussioncontrasting
confidence: 56%
“…However, in the present study, the increased ITE seen in plants grown in elevated CO 2 was probably more attributed to an increased competitiveness of CO 2 against O 2 for the active site on the Rubisco protein, which was also suggested as the main effect of elevated CO 2 on photosynthesis in carrot (Thiagarajan et al. ).…”
Section: Discussionmentioning
confidence: 41%
“…1). The trends observed in this study were comparable to those observed during our previous studies (Thiagarajan et al 2007).…”
Section: Resultssupporting
confidence: 92%
“…The two major environmental parameters that change with planting and harvesting time are ambient air temperature and photosynthetic photon flux density (PPFD). The relationship between PPFD (Kyei-Boahen et al 2003), temperature (Thiagarajan et al 2007) and P N has been investigated in carrots (Daucus carota L.), nevertheless, under noncompetitive and/or controlled environments. High plant densities arising from high seeding rates under field conditions enforce resource limitations particularly, in terms of water, nutrients, and light (Rajasekaran et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In general, photosynthesis can be negatively affected by salt stress due to the decrease of CO2 availability for Rubisco IV INOVAGRI International Meeting, 2017 activity (Hura et al, 2007); as well as decreases in the efficiency of biochemical processes, such as the low electron transport through the electron transport chain of the chloroplast and the inhibition of the activity of several enzymes related to CO2 assimilation (Wise et al, 2004;Thiagarajan et al, 2007). Herein, saline stress significantly reduced the photosynthetic rate of Catissol, BRS 323, BRS 324, H360 and H25 plants, with the most strongly effects in Catissol genotype, whereas no significant changes were registered in the BRS 321 genotype (Figure 2).…”
Section: Resultsmentioning
confidence: 99%